The rise or fall of world inequality: A superious controversy? - Bart Capéau; André Decoster (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
In the age of globalization, the question whether inequality in the world rose or fell down, is a hot topic. Leading scholars in the field of economic inequality measurement developed methods to estimate empirically the distribution of welfare (income) amongst world citizens. Despite their similar methodologies, they do not seem to agree about the conclusion. In the present paper we pinpoint what drives the two extreme positions apart. Sala-i-Martin (2002a, b), who claims that there can be no doubt that world inequality went down between the late 1970s and the late 1990s, has in fact calculated population weighted inequality between countries. Milanovic (2002a, b, c) does not deny this, but illustrates the empirical importance of divergent tendencies at the sub-national level (especially urban versus rural regions) for assessing true world inequality and comes to the reverse conclusion. Nevertheless, there seems to be unanimity, especially amongst the contributions quoted here, about the inequality measure(s) to be used for assessing world income distributions. We show that at least for international inequality, there is empirical evidence for rank reversals among the class of generalized entropy measures and expect the same to be true of world inequality. However, the normative debate about which inequality measure to use for assessing true world inequality has not yet begun.
Keywords: D31; D63; O15; 330; inequality; world income distribution; Einkommensverteilung; International; Messung; Theorie; Welt